Evaluation of Snake Bite Cases Admitted To Hospital in Tertiary Care - Avinash H. Waghmode; Pravir Bodkha; Suvarna N.Patil; A.J.Ajankar; Sonali Kotkar (Institute of Medico-legal Publications Pvt Ltd, 2021)
A significant problem faced in rural India is snake bite. India’s high mortality rate is due to climatic conditions,population predominance in rural areas, and agricultural dependency. In order to research the epidemiologyand outcome of snake bite cases, this retrospective study was done at B.K.L Walawalkar Rural MedicalCollege and Hospital, Sawarde. During the study period, 58 snake bite cases were reported.30 of the biteswere poisonous. Male preponderance has been noted.Maximum number of cases were seen during rainyseason and more during day time.The lower limbs were most frequently involved.42 cases were recoveredout of 58 cases and 16 patients left the hospital againstthe medical advice.As a specific treatment, polyvalentAnti Snake Venom (ASV) vials were used. The improvement in mortality may be the consequence of timelyhospitalization and specific care and subsequent first aid steps.